Wyklęta anarchistka. Rzecz o socjalistce Jadwidze Gulińskiej w Poznaniu w początkach XX w. = The excommunicated anarchist - a word about a socialist Jadwiga Gulińska in Poznań in the early 20th century - Wyder, Grażyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The social movement which was developing in the beginning of the 20th century created a number of devoted activists who believed that it would be among others, a means to regain independence. This was happening in the land of annexed territory of Poland. Women were also engaged in the movement. The example of an activist who devoted her health and carcer to the new idea was Jadwiga Gulińska.
Keywords: Gulińska, Jadwiga (1863-1939); socjalizm - aspekt społeczny; Wielkopolska - historia - 19 w.; Wielkopolska - historia - 20 w.